Apparent diffusion coefficient: An associative factor for recurrence after nephrectomy in localized renal cell carcinoma. Issue 1 (16th June 2015) - Nishie, Akihiro; Kakihara, Daisuke; Asayama, Yoshiki; Ishigami, Kousei; Ushijima, Yasuhiro; Takayama, Yukihisa; Okamoto, Daisuke; Fujita, Nobuhiro; Morita, Koichiro; Kubo, Yuichiro; Inokuchi, Junichi; Honda, Hiroshi
Abstract : Purpose: To investigate whether the apparent diffusion coefficient (ADC) of a tumor is associated with recurrence after nephrectomy in renal cell carcinoma (RCC) Materials and Methods: We retrospectively studied 49 patients with localized RCC who underwent 1.5T magnetic resonance imaging (MRI) including diffusion‐weighted imaging preoperatively. Fifteen patients had recurrent disease after surgery. The ADC was measured by placing a region‐of‐interest in a solid region of each tumor on the ADC map. We named the average value of the three ADC values the "average ADC" and the lowest ADC value among the three as the "minimum ADC." The correlations between clinicopathological factors including patient age and gender, tumor side, tumor size, growth/invasion pattern, Fuhrman grade, histological subtype, venous invasion, average and minimum ADCs, and disease‐free survival were analyzed by Cox proportional hazards model. Results: In univariate analysis, tumor size, venous invasion, mean ADC, and minimum ADC showed significant correlations with disease‐free survival ( P < 0.05). In multivariate analysis, only venous invasion and minimum ADC were significant ( P < 0.05). The 5‐year disease‐free survival rate of the low minimum ADC group was 51.6%, while that of the high minimum ADC group was 85.1%. Conclusion: The minimum ADC of a tumor, although not as pronounced as venous invasion, was found to be an independent associative factor for recurrence after nephrectomy in patients with localized RCC. J. MAGN. RESON. IMAGING 2016;43:166–172.